PHARMACOTHERAPY FOR RHEUMATOID ARTHRITIS IN THE 21st CENTURY: FOCUS ON RITUXIMAB - Evgeni Lvovich Nasonov (Современная ревматология, 2009)
Rheumatoid arthritis (RA) is one of the most common and severe chronic inflammatory diseases. The paper reviews the recent studies evaluating the efficacy of rituximab (MabThera®), chimeric anti-CD20 monoclonal antibodies in B cells, in patients with RA. It has been shown that Rituximab is an extremely effective and relatively safe drug for the treatment of RA and may be considered to be a prototype for a new line in the management of autoimmune diseases, the basis for which is B-cell immunity modulation.